Immunocompatibility in transplantation: adapting to a changing therapeutic landscape - Güell-Alonso, Raquel; Cabrera-Pérez, Raquel; Vives, Joaquim (Frontiers in Immunology, 2025)
The ongoing shortage of cell, tissue, and organ donors has led to prioritizing clinical urgency over optimal immune matching in transplantation, often at the cost of increased reliance on immunosuppressive regimens and their associated adverse effects. Recent advances in the use of Substances of Human Origin (SoHOs), xenotransplantation and emerging cell-, gene-, and tissue-based therapies have enabled the development of tailored cellular therapeutics to enhance engraftment, long-term function, and immunological compatibility. Within this evolving context, artificial intelligence is also increasingly contributing to improve donor–recipient matching through predictive analytics and integrative data modeling, assisting on immune tolerance and the durable integration of transplanted cells into host tissues. In this review, we revisit foundational concepts of immunocompatibility, examine current clinical criteria in organ transplantation, and critically explore the shifting paradigms of donor–recipient matching in the era of personalized medicine. These advances have the potential to redefine clinical strategies in transplantation and regenerative care while ensuring patient access and sustainability.